ACCESS OF INDIVIDUALS TO MERCOSUR TRIBUNALS: FILLING THE GAP VIA ADVISORY OPINIONS - Almeida, Paula Wojcikiewicz (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2018)
The Mercosur dispute settlement system possesses several limitations, which are linked to its transitory aspect and include, in particular, the limited access of individuals who are only able to present their demands via the National Section of the Common Market Group of the member state in question. The application of the advisory opinions’ mechanism embodies a possible alternative in order to overcome the lack of access of individuals and civil society to Mercosur Tribunals. The referred mechanism enables national courts to question the Permanent Review Court exclusively with regards to the interpretation of Mercosur law. Therefore, it guarantees an indirect access of individuals to Mercosur Tribunals. However, there is still a very low number of advisory opinions solicited to the PRC, which are due, among other factors, to the lack of knowledge of Mercosur law and its mechanisms by lawyers and national judges. This challenged is combined with a normative limitation, i.e., the double non-binding character of the advisory opinions, thereby contributing to legal uncertainty. Some alternatives have been envisaged, notably with the creation of a permanent court for Mercosur.